A Powerful Consistency Methods for Sensor Nodes Reconstruction to Enhanced the Consumed Energy of Wireless Sensor Networks - Aqeel K. Kadhim (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Enhancing consumed energy in WSNs is prime issue, clustering is one of the main techniques that are utilizing for decreasing the energy dissipation in WSN. A Fuzzy C-Mean Clustering (FCM) algorithm is proposed as one of the important methods adopted in the clustering field. Voronoi diagram technique are contribute with FCM method to reduce the intra-clustering distance. Decision tree algorithm (DTA) is also utilized as a useful method to select high-specification sensor nodes a Custer Head (CH). This collection of algorithm and methods will has given momentum to improve network status and has an effective influence on the decreasing of consumed energy and increasing of network efficiency. The aforementioned methods, have further contributed to up growth of a new schema, which has been called Improved Voronoi Fuzzy Clustering System (IVFCS). Voronoi diagram technique that applied to split the monitoring region into a number of Voronoi position called cells, are been engaged with FCM method in order to decrees the intra-clustering communication. Decision Tree Algorithm (DTA) which is a class of supervised machine learning algorithms, that have been used professionally for the purpose of CH selecting based on the parameters of: node residual energy, distance between CH with its neighbor sensors and packet loss values. The CH electing is done in such a way that reduces the distance of communication and participate in restrict the consumed energy amount in the entire network. The unification of the above three powerful methods and their contribution towards the better choice of cluster head has led to construct an improved VFCS schema. The support of the three effective methods is to reduce consumed energy and maintained the data routing process within the network. As a result, this was effectively reflected in the continuation of network performance for a longer period if compared with well-known protocols in the field of WSNs, for example (LEACH, MOD-LEACH, SEP, Z-SEP and DEEC protocols).